1984
DOI: 10.1111/j.1469-8137.1984.tb02732.x
|View full text |Cite
|
Sign up to set email alerts
|

GENOTYPIC VARIATION IN THE RESPONSE TO SUB‐OPTIMAL TEMPERATURES OF GROWTH IN TOMATO (LYCOPERSICON ESCULENTUM MILL.)

Abstract: SUMMARYA growth analysis of plants raised under controlled environment conditions was used to examine the response to temperature of five contrasting tomato cultivars bred for outdoor production. Curves were fitted to the data of dry weight and leaf area and, to compensate for ontogenetic drift, instantaneous values of growth analysis parameters were calculated from these curves at a specific growth stage. Differences in relative growth rate which could be exploited in a breeding programme were not detected, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…a high photosynthetic activity per unit leaf area or a large photosynthetic area. This was also observed in other genotypes of tomato by PAUL et al (1984). Genotype x temperature interactions.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…a high photosynthetic activity per unit leaf area or a large photosynthetic area. This was also observed in other genotypes of tomato by PAUL et al (1984). Genotype x temperature interactions.…”
Section: Discussionsupporting
confidence: 58%
“…Large differences between genotypes were found in total dry weight which have to be attributed to the differences in plant weight at the Euphytica 35 (1986) start of the experiments. From a growth analysis of five outdoor tomato genotypes, differing in cold tolerance, which were grown at a range of temperatures and a high light intensity, PAUL et al (1984) concluded that variation in seed weight is an important factor in the genotypic variation of plant weight. In the present experiments a positive correlation between seed weight and plant weight was only found in two of the three experiments.…”
Section: Discussionmentioning
confidence: 99%
“…As the environmental cultivation conditions were performed with only one cultivar, it could also be that using other cultivars might lead to significant differences in allergenic potential if grown under different conditions. However, this seems not very likely, because the variation in adaptability to environmental conditions is small among different tomato cultivars as a consequence of inbreeding during domestication 25, 26…”
Section: Resultsmentioning
confidence: 99%
“…Complex traits generally are of rather low heritability, more frequently because of excessive environmental effects than lack of genetic variation. Paul et al (1984) analyzed components of growth of five cultivars under controlled environments, but no differences in these components were useful in breeding. Bernier and Ferguson (1962) selected high-yielding, large-fruited tomato lines by focusing on early fruit set and the size of the first four ripe fruit.…”
Section: Linkage and Genetic Correlationmentioning
confidence: 99%